Study on the gasification of biochar without smoke - YANG, Por; LASY, Alonny; SOULISOMBOUN , Dee; RASAVONG, Sibounheng (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The main purpose of this investigation was to examine the methods of charcoal burning and process of the production of charcoal without smog through the use of recyclable materials, for example, wood chips which are found in the community to gasify the process and convert the wood into high quality bio-char or charcoal which is deemed as safe for consumption. This research was conducted as an experiment at the faculty of engineering, SouphanouvongUniversity via the use of iron tank of 200 liters to construct the tank for burning charcoal with wood chips from sawmill. The findings of this investigation found that the process of burning biochar without smoke was gasification process and wood for burning charcoal can be easily found locally. While burning, there was no smoke affecting people residing nearby as burning process was the complet combustion that contained syngas and charcoal which are found to eco-friendly or environmentally-friendly. Whilst combusting, the temperature was gradually increased from the start, but slowly decreased because of burning tank completing combustion and the highest of the wood combustion was 1022ºC. As a result, biochar can be used in a number of ways, for example, cooking, water boiling and treatment, mitigation of climate change, carbon sequestration, mitigation of green house gas emissions and it can be also mixed with fertilizer used in agricultural production. Therefore, even though burning charcoal, one of the small activities which are localy practiced in the rural areas, it is one of the alternative source of energy which can be used to mitigate and minimize the impact of environmental issues.